ELEVATING FISHEaS OF DAL IN J SH - Ojha, S. N.; Biradar, R. S.; Shah, Tasaduq H.; Ali, Shaukath (Journal of Indian Fisheries Association, 2015)
The deteriorating condition of one of the most magnificent lakes of India, the Dal Lake, has provoked a lot of research interest from the biological and ecological points of view. However, the impact of deterioration of the ecology on the inhabitant fisherfolk around Dal Lake has not been given much importance. In this study, the three major beats of the lake, namely, Hazratbal, Nishat and Nehru Park, were surveyed, randomly taking 10% of the fishermen families. It was observed that the summer mean catch per day (5.18 t 0.69 kg) was more than the mean winter catch per day (2.85 t 0.40 kg). However, the total annual catch per person was only 1195.56 t 211.63 kg. Moreover, marketing through middlemen, especially, during summer, was observed to be very low fetching in terms of mean price per kilogramme fish, amounting to Rs 37.50 t 2.54 for local fish and Rs 22.50 t 2.88 for the carp. It was also observed that the fisherfolk had borrowed a good amount of money for the repair and construction of their houses and boats. Therefore, on the whole, the fishing business around Dal Lake was observed to be under severe stress. In this context, this paper has come out with recommendations to uplift the socio-economic conditions of the fishers. Key words: Dal Lake, socio-economics, fisherfolk